Campus Social Responsibility: Program Policy Strategy In Protecting School Droppouts - Wakhid, Ali Abdul; Qohar, Abd; Faizal, Liky (Universitas Islam Negeri Raden Intan Lampung, 2024)
The issue of school dropouts remains an unresolved problem to this day. The Campus Social Responsibility program is an initiative aimed at addressing school dropout issues in Lampung Province, in line with the implementation of Lampung Governor Regulation No. 1 of 2021 on Child Protection. This study explains the policy strategies of the Campus Social Responsibility program in protecting school dropouts in Lampung Province. The research uses a qualitative approach with a multiple case design and a single-unit analysis. Data were collected through in-depth and group interviews as well as document analysis. In-depth and group interviews were conducted with 15 subjects. Data was also gathered through document analysis of various policy documents related to the Campus Social Responsibility program for the protection of school dropouts. The results of the study show that there are three policy strategies of the Campus Social Responsibility program in protecting school dropouts in Lampung Province: monitoring, facilitating the payment of education fees for underprivileged children. The impact of the Campus Social Responsibility program's policy implementation in protecting school dropouts in Lampung Province has brought about changes, including a reduction in the number of school dropouts, children at risk of dropping out, unemployment, and poverty. Keywords: Program, CSR, school dropouts